2021
DOI: 10.3390/jcm10112499
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies by University Students in Response to COVID-19: Differences between Community and Clinical Groups

Abstract: Last year, the COVID-19 pandemic had severe consequences on the health and well-being of millions of people. Different studies try to identify the main effects that the crisis and several lockdowns have had on the citizens’ mental health. This research analyses the coping strategies generated by students from a community group and a clinical group in response to this crisis, using the Coping Responses Inventory—Adult Form (CRI-A) by Moos with a sample of 1074 students of Universidad de Extremadura. Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Current research suggests that interventions aimed at reducing academic stress and teaching effective coping strategies may be effective in preventing and reducing depression among college students (López-Ramos & Mendo-Lázaro, 2021;Babicka-Wirkus et al, 2021). Cognitive-behavioral therapy (CBT) is one such intervention that has been found to be effective in reducing depression symptoms among college students (Hofmann et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Current research suggests that interventions aimed at reducing academic stress and teaching effective coping strategies may be effective in preventing and reducing depression among college students (López-Ramos & Mendo-Lázaro, 2021;Babicka-Wirkus et al, 2021). Cognitive-behavioral therapy (CBT) is one such intervention that has been found to be effective in reducing depression symptoms among college students (Hofmann et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Scholars have also found that lockdown affects different individuals in different ways and to different degrees. Many of them have compared the level of various mental health indicators measured in cross-sectional surveys conducted in the general population ( 15 ), Child ( 16 ), adolescents ( 17 ), adults ( 18 ), older adults ( 19 ), new mum ( 20 ), university students ( 21 ), and college students ( 22 ). For example, Yildirim ( 19 ) identified the psychosocial status, attitudes, and experiences of individuals aged 65 and older confined in their homes during the COVID-19 outbreak in Turkey, and concluded that lockdown applied specifically to older adults forced them to establish new routines and made them aware of some values; however, they asserted that they were stigmatized and isolated, their fear of COVID-19 increased, and they were treated unfairly.…”
Section: Introductionmentioning
confidence: 99%